2011
DOI: 10.1021/je200486c
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Prediction of the Temperature-Dependent Henry's Constant for CO2–Ionic Liquid Systems Using the Conductor-like Screening Model for Realistic Solvation (COSMO-RS)

Abstract: Henry's constant H of carbon dioxide in a number of ionic liquids (ILs) has been studied using the predictive method COnductor-like Screening MOdel for Realistic Solvation (COSMO-RS). Experimental H values for 14 CO2–IL systems spread over a temperature range of (283 to 333) K have been used to estimate the parameters λ1 and λ2 of the combinatorial term to calculate the chemical potential. The H values of CO2 in 18 other ILs have been validated and found to be in good agreement with the experimental data with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 39 publications
2
36
0
Order By: Relevance
“…Interestingly, imidazolium-based ILs exhibited remarkable CO2 capture capacity (Anthony et al, 2002;Kamps et al, 2003;Husson et al, 2010). Semi-empirical studies were also conducted to determine the Henry constant of several ILs (Mortazavi-Manesh et al, 2011;Sistla and Khanna, 2011). Overall, it was found that the shape and size of ILs played a major role in the value of the Henry constant of ILs.…”
Section: Conventional Ionic Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, imidazolium-based ILs exhibited remarkable CO2 capture capacity (Anthony et al, 2002;Kamps et al, 2003;Husson et al, 2010). Semi-empirical studies were also conducted to determine the Henry constant of several ILs (Mortazavi-Manesh et al, 2011;Sistla and Khanna, 2011). Overall, it was found that the shape and size of ILs played a major role in the value of the Henry constant of ILs.…”
Section: Conventional Ionic Liquidsmentioning
confidence: 99%
“…They revealed that the anions played a critical role in interacting with CO2 (Cadena et al, 2004 (Anthony et al, 2005). Among the anions, those with fluoride have drawn significant interest (Aki et al, 2004;Bara et al, 2009;Sistla and Khanna, 2011). For instance, a detailed study on the effect of anions on CO2 capture was conducted focusing on the influence of fluorination on CO2 solubility in ILs (Aki et al, 2004…”
Section: Conventional Ionic Liquidsmentioning
confidence: 99%
“…To better understand the relationship between monomer structure and reactivity, the volume contributions of the nonpolymerizable monomer substituents were calculated using COSMOtherm, a thermodynamics software program that has previously been used to estimate IL properties . Using a set of 71 imidazolium‐based PIL monomers and NPILs with the Tf 2 N − anion, a regression analysis was used to model the volume contributions of different functional groups (e.g., vinyl, methylene groups) to the molar volumes of the monomers in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Using TURBOMOLE, density functional theory (DFT) level calculations were used to obtain optimized structures for a series of 71 imidazolium cations with the Becke–Purdew (b–p) functional and the triple ζ valence polarization (TZVP) basis set . The computational thermodynamics software package COSMOtherm (v. C30_1301) was used to calculate molar volume for the series of ILs composed of these cations and the [Tf 2 N] − anion at the TZVP level, consistent with previous work using this software package to investigate IL properties . Numerical values corresponding to the number of functional groups were assigned to each IL and a regression analysis was used to determine molar volume contributions of IL structural components.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, one can still expect to obtain useful trends from such calculations. There have been several recent reports on COSMO-RS computation of CO 2 solubility in different ILs [70][71][72][73][74] with the aim of uncovering trends that can serve as a guide to solvent optimization.…”
Section: Screening Of Ils For Co 2 Capture Efficiencymentioning
confidence: 99%